Self-awareness and the evaluation of hot flash severity: observations from the Seattle Midlife Women's Health Study. Issue 5 (May 2019) - Taylor-Swanson, Lisa Jean; Pike, Kenneth; Mitchell, Ellen Sullivan; Herting, Jerald R.; Woods, Nancy Fugate
Abstract: Objective: The purpose of this study was to test the association of two dimensions of self-awareness with hot flash (HF) severity. Methods: A subset of women from the Seattle Midlife Women's Health Study (N = 232) provided data for these analyses. Structural equation modeling was used to evaluate two dimensions of self-awareness (Internal States Awareness [ISA] and Self-Reflectiveness [SR]), and secondary factors of perceived stress, anxiety, and attitudes toward menopause as continuous with earlier life, health perceptions, and menopausal stage with respect to HF severity. The measurement and structural models were tested with a maximum likelihood missing values estimator and displayed good model fit. Results: Women with greater ISA reported greater HF severity (β = 0.17, P < 0.05). In addition, women in later menopausal transition stages reported greater HF severity and those with attitudes of continuity toward menopause reported less severe HFs (β = 0.20, P < 0.01, β = −0.30, P < 0.001, respectively). SR was not related to HF severity. Women with higher levels of SR reported greater perceived stress levels (β = .51, P < 0.001), and those with greater perceived stress reported greater anxiety levels (β = 0.63, P < 0.001) and attitudes of continuity toward menopause as less continuous with earlier life (β = −0.30, P < 0.001). Conclusions: ISA (balanced self-awareness) was associated with greater HF severity, suggesting that enhanced balanced self-awareness may promote women's ability to evaluate their symptom experience. A multidimensional construct of self-awareness, perceived stress, anxiety, and attitude toward menopause are all plausible targets for future intervention studies of symptom management.